Changes in glaucoma medication numbers after cataract and glaucoma surgery: A nationwide population-based study. Issue 4 (January 2019) - Chen, Hsin-Yi; Lin, Cheng-Li; Kao, Chia-Hung
Abstract : Abstract: To determine whether cataract or glaucoma and combined cataract and glaucoma surgery (CGS) affect glaucoma medication usage. We recruited patients who received new diagnoses of glaucoma, either primary open-angle glaucoma (POAG) (International Classification of Diseases, Ninth Revision, Clinical Modification [ICD-9-CM] code 365.1) or primary angle-closure glaucoma (PACG) (ICD-9-CM code 365.2), between 1998 and 2011 and had undergone cataract surgery alone (CS), glaucoma surgery alone (GS), or CGS under the National Health Insurance program in Taiwan. CS, GS, and CGS in all the patients were performed after the glaucoma diagnosis date. The patients were subdivided into CS, CGS, and GS groups. The number of glaucoma medications, including prostaglandin analogs, β-blockers, carbonic anhydrase inhibitors, α-agonists, pilocarpine, and a combination of drugs, in each prescription, were compared before and after surgery. The mean number of glaucoma medications in each prescription before the surgery increased from approximately 0.5/1 (CS/CGS + GS) to a peak of 1.75/3 within 3 months before the index date. The mean number of glaucoma medications in each prescription reduced to 0 (CS group) and to approximately 0.5 (CGS and GS) at the end of the 3-year follow-up period. The mean number of glaucoma medications in each prescription significantly reduced at the time points within 6 months, between 6 months and 2 years, and during 2 to 3 years after surgery in each group. At the end of the 3-year period, the reduction effect was most evident in the CS group. Similar trends were also observed in the POAG and PACG group. CS, GS, and CGS significantly reduced the number of glaucoma medications used by the glaucoma patients.